HUBUNGAN ANTARA PAJAK PENERANGAN JALAN DAN KUALITAS LAYANAN PENERANGAN JALAN UMUM DI KOTA BATAM - , Raden Mas Andreas Purwihandoko ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Street Lighting Tax (PPJ) is one source of local revenues through local taxation sector. PPJ in Batam always show improvement from year to year. Under applicable law, the PPJ has implications for providing PJU services in the local area. In terms of the PJU development plan, Batam City Government only see the role and function of the factors of a region without involvement of subjectfactors, contribution or payment levels of productivity through the PPJ. This study aims to examine the correlation between income ofPPJ and quality of PJU service which are represented by the public response. The variables used in this research are: income PPJ, the number of distribution points PJU in all districts in Batam city and the public response of PJU service quality. Technical analysis is performed by the mixed methods, namely quantitative and qualitative. Non-parametric statistical test used Spearman rank to see the correlation between income of PPJ and thepublic response of PJU servicequality. Qualitative methods such as depth interviews are used as support in analyzing this relationship. The study show that: (1) between the income of PPJ and the number of PJU points has a very strong relationship and significant, (2) the income of PPJ and public response of PJU service quality has a very strong relationship and significant. These findings suggest that the accumulation of PPJ income in an area can be used as a basis by the Government of Batam in determining the next PJU planning.